Identification of Availability and Lignocellulosic Properties in Coconut Dregs Waste - Murtius, Wenny Surya; Argo, Bambang Dwi; Nurika, Irnia; Sukardi, Sukardi (Green Engineering Society, 2024)
Agricultural waste, including coconut pulp, contains lignocellulose and is a very important, renewable and sustainable industrial raw material. Many of the food, textile, pharmaceutical, paint and resin, agrochemical, oil processing, and other sectors utilize lignocellulosic derivatives. The objectives of this study were to determine the availability of coconut pulp in Padang City-West Sumatra, analyse the lignocellulosic components contained and cell surface morphology, and observe the chemical elements in coconut pulp waste. An exploratory approach was used in this study to achieve these objectives. The results showed that there were 98 coconut milk entrepreneurs spread across traditional markets in Padang City, West Sumatra. Every day the coconut milk squeeze business examined produces ± 1.18 tonnes of coconut pulp. Coconut waste also contains 47.18% cellulose, 10.58% lignin, and 12.10% hemicellulose. Based on the XRD results, the crystal size of coconut pulp obtained from XRD observation is 11.8 nm.